Intra-His bundle block: clinical, electrocardiographic, and electrophysiologic characteristics - Andréa,Eduardo M. (2002)
OBJECTIVE: To assess the clinical, electrocardiographic, and electrophysiologic characteristics of patients (pt) with intra-His bundle block undergoing an electrophysiologic study (EPS). METHODS: We analyzed the characteristics of 16 pt with second-degree atrioventricular block and symptoms of syncope or dyspnea, or both, undergoing conventional EPS. RESULTS: Intra-His bundle block was documented in 16 pt during an EPS. In 15 (94%) pt, the atrioventricular block was recorded in sinus rhythm; 4 (25%) pt had intra-His Wenckebach phenomenon, which correlated with Mobitz I (MI) atrioventricular block on the electrocardiogram. Seven (44%) pt had 2:1 atrioventricular block, 2 of whom were asymptomatic (12.5%). One (6%) pt had intra- and infra-His bundle block. Clinically, 11 (68%) pt had syncope or presyncope, 3 (18%) had dyspnea on exertion, and 2 (12.5%) were asymptomatic. Eight (50%) pt had bundle-branch block as follows: 4 (25%) pt had left bundle-branch block, and 4 (25%) had right bundle-branch block. Left anterosuperior divisional block was observed in 3 pt (19%), 2 of whom with associated right bundle-branch block. CONCLUSION: Intra-His bundle block was observed in 11% of the pt with second-degree atrioventricular block, syncope or presyncope, or both, it being the most frequent clinical presentation. Intra-His bundle block was more common in the elderly (> 60 years) and among females. The most frequent electrocardiographic presentations were second-degree Mobitz I or type 2:1 atrioventricular block.